Physical Exertion Immediately Prior to Placental Abruption: A Case-Crossover Study. Issue 10 (9th July 2018) - Chahal, Harpreet S; Gelaye, Bizu; Mostofsky, Elizabeth; Sanchez, Sixto E; Mittleman, Murray A; Maclure, Malcolm; Pacora, Percy; Torres, Jose A; Romero, Roberto; Ananth, Cande V; Williams, Michelle A
Abstract: While there is consistent evidence that episodes of physical exertion are associated with an immediately higher risk of acute ischemic vascular events, the risk of placental abruption immediately following episodes of physical exertion has not been studied. In a multicenter case-crossover study, we interviewed 663 women with placental abruption at 7 Peruvian hospitals between January 2013 and August 2015. We asked women about physical exertion in the hour before symptom onset and compared this with their frequency of physical exertion over the prior week. Compared with times with light or no exertion, the risk of placental abruption was 7.8 (95% confidence interval (CI): 5.5, 11.0) times greater in the hour following moderate or heavy physical exertion. The instantaneous incidence rate ratio of placental abruption within an hour of moderate or heavy physical exertion was lower for women who habitually engaged in moderate or heavy physical activity more than 3 times per week in the year before pregnancy (rate ratio (RR) = 3.0, 95% CI: 1.6, 5.9) compared with more sedentary women (RR = 17.3, 95% CI: 11.3, 26.7; P for homogeneity < 0.001), and the rate ratio was higher among women with preeclampsia/eclampsia (RR = 13.6, 95% CI: 7.0, 26.2) than among women without (RR = 6.7, 95% CI: 4.4, 10.0; P for homogeneity = 0.07).